FACTORS ASSOCIATED WITH LONELINESS AMONG OLDER ADULTS LIVING IN LOW-INCOME INDEPEDENT HOUSING - Bonifas, R.P. (Innov Aging, 2017)
Among older adults the experience of loneliness can negatively influence physical health, mental health, and psychosocial functioning. Although considerable literature provides a foundation for understanding loneliness among diverse older population groups, limited work has focused on loneliness among older adults living in independent low-income housing. As part of a larger study examining health and social outcomes among residents in one urban setting, an interactionist theoretical lens was used to assess relationships between loneliness and emotional well-being, health and physical functioning, social connectedness, and sense of community among older adults in the sample (n =44). The primary aim of analysis was to identify promising points of intervention to address loneliness. Findings reveal high levels of loneliness with 48 percent endorsing frequent to severe loneliness per the UCLA Loneliness Scale. Multiple linear regression results indicated that the four independent variables predict 28.2 percent of the variance in loneliness (f = 5.142; p < .002), but neither social connectedness, as measured by the Lubben Social Network Scale, or sense of community, as measured by the Sense of Community Index II, were associated with loneliness. However, lower quality of life due to dissatisfaction with health and physical functioning (via Ferrans and Powers Quality of Life Index) and low emotional well-being (via SF-36) were both associated with higher reported loneliness. Findings suggest that loneliness reduction interventions focused on expanding social network connections and community integration might achieve greater leverage if residents are also supported to better cope with health issues, functional limitations, and emotional distress.